Visual and Hormone Outcomes in Pituitary Apoplexy: Results of a Single Surgeon, Single Institution 15-Year Retrospective Review and Pooled Data Analysis - Seaman, Scott C.; Dougherty, Mark C.; Zanaty, Mario; Bruch, Leslie A.; Graham, Scott M.; Greenlee, Jeremy D. W. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Introduction Pituitary apoplexy commonly presents with visual and hormonal deficits. While traditionally regarded as an emergency, there have been increasing trends toward conservative management. Our institutional practice consists of early surgery; therefore, we reviewed our series evaluating vision outcomes, hormone function, and complications compared with the present literature.Methods We retrospectively reviewed our institution's medical records to identify pituitary apoplexy patients who were treated via the endoscopic endonasal approach by a single neurosurgeon (senior author). We recorded basic demographics, radiographic and operative features, and preoperative and postoperative vision and hormone status. Univariate and multivariate statistical analyses were performed. Pooled data analysis of visual outcomes in the current literature using Bayesian inference was performed.Results We identified 44 patients with histologically confirmed pituitary apoplexy treated by endoscopic transsphenoidal decompression; 77% were treated within 24 hours of presentation. Total 45% had cranial nerve (CN) palsy, 36% anopsia, and 20% had visual acuity deficits. Postoperatively, 100% of CN palsies improved, 81% of anopsias improved, and 66.7% of visual acuity deficits improved. Long-lasting panhypopituitarism (25%) and hypothyrodism (22%) were common. Cavernous sinus involvement predicted residual tumor (p = 0.006). Pooled Bayesian inference showed 30% improvement in vision outcomes with surgical management compared with medical management with a number needed to treat of 3.3.Conclusion Early surgery for pituitary apoplexy was associated with excellent visual outcomes and the need for long-term hormone replacement is common. Cavernous sinus involvement is an independent predictor of residual tumor. Pooled statistical analysis favors aggressive surgical management of apoplexy for improved visual outcomes.
Keywords: hormone dysfunction; hypopituitarism; vision outcomes; aggressive early surgery; timing of surgery; pooled analysis